The Product Patent and its Impact on Working Capital Management of Ranbaxy Laboratories Limited - Jana, Kajalbaran (Indian Journal of Finance, 2011)
With the advent of economic reforms in India, various changes had been started, which affected various industries by virtue of various reformist actions. The Indian pharmaceutical companies also undertook such reforms. The paradigm shift from ’process patent’ to ’product patent’ is the outcome of Trade Related Intellectual Property Rights (TRIPS) under GATT agreement signed during 1994 by India, which was also initiation of economic reform in this field. The Ranbaxy Laboratory occupied the largest position in terms of market share and although, it had other definite favorable conditions, still, during product patent period, the working capital management of this company has worsened. The liquidity, operational efficiency and ultimately, the profitability had declined during the period. The credit worthiness, interest rate deregulation, money and debt market reconstruction, cautious cash management and ultimately, the competitive endeavor that actually pointed out for better management of working capital of the domestic company under financial sector reforms have been found to be ineffective, rather say destructive, for a company like Ranbaxy, who was a giant in pharmaceutical industries in domestic as well as international market. The company incurred huge losses in the year 2008, for the first time since its inception. It is no doubt analysis on the basis of three years performance is not sufficient enough to make a concluding remark, still in view to pro-verb ’morning shows the day’, it can be said that product patent may create enough scope for better performance for the beginners, but not for the established firms like Ranbaxy. In this paper, the author tried to outline the state of working capital management of Ranbaxy Laboratories Ltd. during product patent and before product patent and their provides direction for probable causes for further research.